A (crooked) mirror for knights – the case of Dinadan - Witalisz, Władysław (Adam Mickiewicz University, 2008)
The picture of chivalry in medieval romance was primarily an idealised vision of knightly custom. The world of King Arthur and Camelot codified moral and courtly standards which were presented in literature as patterns for emulation. The writings of Sir Thomas Malory, the last medieval bearerup of Camelot, was understood and received by medieval readers as a traditional praise of chivalry. It is therefore especially intriguing to find in the Morte Darthur the irreverent figure of Dinadan, a knight more ready for a jest rather than a joust, a clown whose words and deeds ridicule chivalric customs. His light treatment of chivalric norm and of courtly love sets him apart from the otherwise traditionally-minded Camelot. On the one hand, Dinadan may be viewed as Malory’s touch of comedy and common-sense in his late medieval treatment of the old, quaint world. On the other hand, Dinadan’s irreverence may be seen as a serious breach in the otherwise didactically idealised image of Arthur’s Britain. The presence of Dinadan complicates the moral appeal of Malory’s Camelot and brings a dose of ambivalence and a lack of clear didactic closure into the text.